(untitled) (Acta Scientiarum. Agronomy, 2021)
Seed coat characteristics may be related to seed quality and longevity, attracting the interest of breeding programs. This study aimed to evaluate the relationship between the water absorption parameters and storage tolerance of soybean seeds with contrasting seed coat characteristics. For this purpose, seeds of five soybean cultivars with different seed coat colors and lignin contents were used. Before storage, the seed coat lignin content, moisture content, water absorption rate in 11 hydration periods (1, 2, 3, 4, 5, 6, 7, 8, 24, 32, and 48 hours), hydration speed index, germination, viability, and seed vigor were determined. After six months of storage in a dry and cold chamber (at 11ºC and 54% relative humidity [RH]) and uncontrolled environment (at 25ºC and 71% RH), the seeds were evaluated for germination, viability, and vigor to quantify changes in their physiological quality during storage and relate them to the seeds water absorption parameters for the different cultivars. The seed coat lignin content is negatively correlated with the seeds water absorption parameters. Soybean cultivars have different storage tolerance levels. Seeds that absorb larger amounts of water have lower tolerance to deterioration related to temperature and relative humidity fluctuations that occur in storage under uncontrolled conditions, negatively affecting the physiological potential of seeds.